Social Security Reform and the Surveillance State: Exploring the Operation of 'Hidden Conditionality' in the Reform of Disability Benefits Since 2010. Issue 2 (24th November 2016) - Manji, Kainde
Abstract : The application of formal conditionality to address 'dependence' on social security has been an important trend since the 1990s. Reforms between 2010 and 2015 saw a renewed interest in this approach. This article will focus on conditionality in disability benefits in that period. It will present findings from a qualitative study of twenty-three disabled people living in the central-belt of Scotland, exploring the operation of surveillance as a form of 'hidden conditionality'. It will find that this had a significant impact on participants' daily lives, affecting who they interacted with, and what activities they felt they could take part in. The implications of this for disabled people's ability to realise equal citizenship will be examined.